5-minute Star Wars stories - Schmidt, Rebecca L.; Dworkin, Brooke; Roux, Step̌hane (Comic book artist); King, Trey; Glass, Calliope; Schmidt, Andy, 1976-; Schaefer, Elizabeth (Adaptor); Pilot Studio (Los Angeles : Disney Lucasfilm Press, 2015)
Young readers are invited to join Anakin, Luke and Yoda for an epic collection of 12 stories that can be read in five minutes, adapted from all seven Star Wars films, including Star Wars: The Force Awakens!
Race to the finish line ; Yoda and the count ; The last adventure / Rebecca L. Schmidt -- Escape from Darth Vader / written by Brooke Dworkin and illustrated by Stephane Roux -- Destroy the Death Star! / Trey King -- The Battle of Hoth / Calliope Glass -- A Jedi, you must become / written by Andy Schmidt and illustrated by Stephane Roux and Pilot Studio -- Rescue from Jabba's palace ; Ewoks join the fight / Brooke Dworkin-- A friend for Rey ; Rathtars on the loose! / written by Elizabeth Schaefer
s"Unless otherwise noted, all illustrations by Pilot Studio"--Title page verso.
Ages 6-8.
Keywords: Imaginary wars and battles -- Juvenile fiction; Life on other planets -- Juvenile fiction; Space warfare -- Juvenile fiction; Star Wars fiction -- Juvenile fiction; Science fiction -- Juvenile fiction; Adventure stories -- Juvenile fiction; Short stories -- Juvenile fiction